APOPLECTIC CORTICOTROPIN-PRODUCING MACROADENOMA: A RARE ENTITY - Shudim, Saiful Shahrizal; Thambirajah, Amrrit Cumarr K; Bidin, Mohamed Badrulnizam Long; Rajoo, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Pituitary tumour apoplexy is defined as infarction, haemorrhage or combination of both occurring in a pituitary tumour as a result of expansion of the tumour causing altered sensorium, visual and ophthalmic 0disturbances and hormonal deficiencies. It is uncommon and mostly happens in macroadenomas. The prevalence of apoplexy is extremely rare in corticotropin-producing adenoma. RESULTS We present a 24-year-old female with persistent Cushing’s disease since 2019 despite transsphenoidal surgery and treatment with high-dose cabergoline. She experienced new-onset left complete ptosis with right ophthalmoplegia few months after surgery. Pituitary MRI showed expansion of the sella toward the left cavernous sinus hence tumour debulking and decompression surgery was planned. However, her serial cortisol and ACTH rapidly declined and dropped to below the reference ranges a few days prior to the planned surgery. Repeat image-guide setting MRI of the pituitary showed features of apoplexy. She underwent successful pterional craniotomy & debulking of the tumour with steroid cover perioperatively. Her postoperative course was uneventful. She was discharged with hydrocortisone. CONCLUSION Corticotropin-producing pituitary macroadenoma is very uncommon and apoplexy following high dose of cabergoline may happen despite the rarity of its incidence.